Stem Xylem Moisture Dinamics in Rosaceae Fruit Trees (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The features of stem xylem moisture in the different fruit trees were studied with using new method offered by authors. Comparing the results one can see that xylem moisture’s deficit differs considerably in species studied: plum trees - 52- 68%; the sweet cherries trees - 34 - 60%; the apple trees 21 - 43%; the peach trees - 20 - 75%; Maximum meaning Dxy in cultures studied are correspondingly: Dxy. = 69%, Dxy. = 61%, Dxy. = 44%, Dxy. = 75% - (accordingly refer to above). The method can be implemented for studying of plant’s water use resistance to the unfavorable environmental factors, as well as in other branches of ecology.
Keywords: xylem, deficit, water use, fruit trees, transpiration rate, Rosaceae.